Analisis Bibliometrik Manfaat Nutrisi pada Sarkopenia: Analisis - Pratiwi, Citra (Cermin Dunia Kedokteran, 2025)
Introduction: The benefits of nutrition in sarcopenia include maintaining muscle mass and improving physical condition. The bibliometric analysis aims to visualize future trends and opportunities for nutritional research in sarcopenia. Methods: Data was gathered from the Scopus database. The BIBLIO checklist is used as a guideline for quantitative analysis of bibliographic data using keywords “diet”, “nutritional approach,” and “sarcopenia”, on literature published between 2015 and 2025. Selection of types, articles, reviews, and conference papers in English, with final or in-press publication status. Studies involving “nonhuman” subjects were excluded. Analysis was conducted using the R and VOSviewer to visualize author networks, keywords, and publication trends. Results: A total of 1,337 documents were found, with 57,860 citations, ranging from 117 to 13,203 document citations per year. H-index is 109. The top three journals were Clinical Nutrition (60 articles), Journal of Nutrition, Health and Aging (44 articles), and Frontiers in Nutrition (33 articles). Publications have increased over the past 10 years. The majority of publications were original articles (60.1%), followed by reviews (38.3%), and conference papers (1.5%). There are 5 clusters of co-occurrence topics from keywords. Conclusion: Research trends focus on sarcopenia prevention. Future studies could explore the effects of vitamin D and the mediterranean diet on sarcopenia.